(untitled) - Sandrieu, Dominique (Paris, 1989)
This book useful because it contains so many expressions that non-French people could not think out. Thus the use of this book leads to a better wording in writing a letter in French language.
Keywords: Letter writing, French,Thư viết, Pháp